Whether Out-of-Bed Activity Restriction in the Early Postoperative Period of PELD Is Beneficial to Therapeutic Efficacy or Reduce Recurrence - Liang, Xiao; Wang, Yexin; Yue, Yaosheng; Li, Yanpeng; Meng, Chunyang (Frontiers in Surgery, 2022)
Objective:To detect the influences of postoperative out-of-bed activity restriction on recurrence rate, low back and leg pain,functional rehabilitation after percutaneous endoscopic lumbar discectomy(PELD). Methods:In this research, 213 patients with lumbar intervertebral disc herniation(LDH) who underwent PELD were divided into out-of-bed activity restriction group and out-of-bed activity non-restriction group.The visual analog scale (VAS) and Oswestry disability index (ODI) scores were used to evaluate postoperative clinical efficacy at 1 month and 3 months after the operation,and to count the recurrence rates.All of these operations were performed between August 2017 to July 2020,and they were followed in the outpatient department for 12 months at least . Results: Both of the groups showed significantly lower VAS and higher ODI scores at 1month and 3months post-operation compared with those pre-operation.At 1month after the operation, the restriction group performed lower VAS scores of low back pain compared with the non-restriction group,but this advantage disappeared at 3months post-operation.However,there was no statistic difference in the VAS scores of leg pain and ODI scores between the two groups,neither at 1month or 3months after the surgery. Recurrence rate is significantly lower in the restriction group than in the non-restriction group at a 12-month follow-up after the surgery. Conclusion:Out-of-bed activity restriction in the early postoperative period of PELD could reduce LDH recurrence effectively,and it may relieve the low back pain to some extent. It has no benefit in the recovery of leg pain and functional rehabilitation.